Exploring Boundaries of Healthcare Roles: The Boundary Work of Hospital Professionals in a Community-Based Health Intervention - Munk, Nicolas Tristan; Schifter Larsen, Trine; Larsen, Kristian; Møller, Tom; Hoxer Brødsgaard, Rasmus; Fisker Rasmussen, Sophia Alberte; Hindhede, Anette Lykke (Professions and professionalism, 2025)
This article examines how hospital-based professionals establish and negotiate their roles without relying on institutional agendas and logics, representing a reconfiguration of professional boundaries through community-based participatory research. Operating outside traditional clinical settings, we examine through interviews and observations how these professionals interact with elderly residents and researchers in shaping a community-oriented role for health professionals. Using Sida Liu’s concepts of boundary making and boundary blurring, the analysis shows how professional roles are actively enacted through individual reflection and collaborative efforts. Instead of simply reproducing or dissolving familiar roles, boundaries are intentionally reaffirmed, adapted, or co-created in response to the specific context and relational dynamics. The findings enhance boundary work literature by highlighting the micro-social and situational aspects of professional role negotiation. The study also prompts broader questions about how hospital-based professionals can engage in community healthcare practices through flexible, participatory approaches.